Alteration in the phagocyte activity of crevicular leucocytes regarding diabetic patients with periodontal disease - Colchado Carhuavilca, Jorge R. (2008)
The goal of this investigation was to find out the alterations in the phagocyte activity of crevicular leucocytes regarding to diabetic patients with periodontal disease. For that reason, 56 patients with periodontal disease were selected: 42 of them with a diagnosis of Diabetes Mellitus - Type 2, and 14 patients without it (control group), from 35 to 74 years old. To performed the study, crevicular fluid of the mentioned patients was analyzed. By means of sequential washings the samples were analyzed microbiological and inmunologically, taking Candida albicans ATCC as indicator of the phagocyte activity. It was found that only a mean of 22.02 (± 7.62) of diabetics crevicular leucocytes group have an adequate phagocyte activity compared to 78.64 (± 9.20) of control group. In the same manner a mean of 78.21 (± 7.84) of diabetics crevicular leucocytes group made adherence without ingestion of C.a. compared to only 21.36 (± 9.20) of the control group. The differences between appropriated phagocytosis and ingestion activity of C.a. diabetics’ crevicular leukocytes group and phagocytes of control group were statistical significant, t = 15.5 (p <=0.001), in the same manner the differences between leukocyte adherence without ingestion of C.a. of diabetic group and the control group, were statistical significant, t = 15.4(p <=0.001).